The readiness of kindergarten teachers in implementing the independent curriculum based on deep learning: A case study in East Kalimantan - Fajriani, Kartika; Hidayah, Lailatul; Santi, Yeni (Privietlab, 2025)
This study aims to examine the readiness of kindergarten (TK) teachers in East Kalimantan to implement the Independent Curriculum based on deep learning, focusing on both conceptual understanding and technical application. A qualitative descriptive approach with a case study design was used. Five teachers from two kindergartens were selected purposively. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using Miles and Huberman’s interactive model (reduction, display, conclusion). All teachers demonstrated a strong conceptual grasp of the Independent Curriculum and deep learning, understood as meaningful and reflective learning. However, the technical readiness varied. Teachers at Handayani 1 Kindergarten, who had attended training, were more capable of designing learning tools aligned with deep learning principles. In contrast, Handayani’s two teachers relied mainly on intuitive practices owing to limited access to training and facilities. Nevertheless, classroom observations revealed practices consistent with the curriculum, including exploratory, experience-based activities, and flexible lesson implementation. This study identifies the phenomenon of teachers’ “intuitive readiness” in curriculum reform, contributing to the theory of teacher preparedness. This suggests the need for continuous reflective training, stronger professional learning communities, and systemic support to enhance deep learning implementation in early childhood education.